Tantangan Guru Dalam Menerapkan Model Pembelajaran PPKN Pada Kurikulum Merdeka - Talita Sembiring; Gadis Prasiska; Kania Nova Ramadhani; Putri Widia Ningsih; Ruth Yessika Siahaan; Salwa Andini; Liber Siagian; Fazli Rachman (Lembaga Pengembangan Kinerja Dosen, 2023)
This study aims to identify and analyze the challenges faced in implementing the Pancasila and Civics Education (PPKn) learning model in the Merdeka Curriculum at SMP Negeri 27 Medan. The research method used is qualitative research with a case study approach. The location of this research is SMP Negeri 27 Medan because this school has adopted the Merdeka Curriculum with a focus on Civics. Data were collected through interviews with Civics teachers, and document analysis related to the curriculum and learning models applied. The results showed several challenges faced in implementing the Civics learning model, including, among others, teachers being required to be more creative to maximize learning design to make it more interesting and so that students do not feel bored and students' resistance to changes in learning approaches. This research provides in-depth insight into the practical and conceptual challenges that need to be overcome to improve the effectiveness of the Civics learning model in the Merdeka Curriculum. The implications of these findings can be used as a basis for developing better educational policies and implementing more effective strategies in facilitating Civics learning at the junior high school level.